NOTES THEORETICAL AND METHODOLOGICAL ON THE WORK BODY OF EDUCATION FULL OF JOÃO BATISTA FREIRE (Fiep Bulletin - online, 2017)
The resistance to biological conception of physical education during the 1980s, leading to criticism of the predominance of sports content in school, so that, as opposed to shed more technical, esportivista and biologist, arise new movements in Physical education, inspired and trailers, it is noteworthy, the social historical moment in which the country passed, education and physical education, coexisting in the area, currently, several pedagogical concepts, which have in common the attempt to break the paradigm of the past. One of them is the Interactionist-Constructivist, the figure of John the Baptist Freire, with his "Full Body Education: Theory and Practice of Physical Education". Therefore, this article aims to discuss aspects (theoretical and practical) Relevant gifts this work because we believe in its theoretical and methodological support, as a resource to support teachers who work or want to work with Physical Education in Early Childhood Education schools (pre-school) and first stage of primary school, for which such work is directed.
Keywords: Physical Education; Child education; Elementary School; Teaching Methodology